2018
DOI: 10.1038/s41467-018-06607-1
|View full text |Cite
|
Sign up to set email alerts
|

The fungal peptide toxin Candidalysin activates the NLRP3 inflammasome and causes cytolysis in mononuclear phagocytes

Abstract: Clearance of invading microbes requires phagocytes of the innate immune system. However, successful pathogens have evolved sophisticated strategies to evade immune killing. The opportunistic human fungal pathogen Candida albicans is efficiently phagocytosed by macrophages, but causes inflammasome activation, host cytolysis, and escapes after hypha formation. Previous studies suggest that macrophage lysis by C. albicans results from early inflammasome-dependent cell death (pyroptosis), late damage due to glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
184
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(203 citation statements)
references
References 78 publications
(157 reference statements)
8
184
3
Order By: Relevance
“…Previous work has shown that C. albicans can switch from yeast to hyphal growth within the nutrient-deprived, acidic phagosome 35 and can escape by rupturing the macrophage membrane during intra-phagocytic hyphal growth 36 . Other mechanisms of escape include the activation of macrophage programmed cell death pathways, including the formation of inflammasomes and pyroptosis 37 , or cell damage induced by a cytolytic peptide toxin (Candidalysin ECE1 ) 38 . Our analysis of single cells revealed bimodal expression in genes involved in these processes, and time analysis suggests that an initial shift in expression of filamentation and cell-wall remodeling programs in phagocytosed C. albicans rapidly result in down-regulation of the pro-inflammatory state of the host cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that C. albicans can switch from yeast to hyphal growth within the nutrient-deprived, acidic phagosome 35 and can escape by rupturing the macrophage membrane during intra-phagocytic hyphal growth 36 . Other mechanisms of escape include the activation of macrophage programmed cell death pathways, including the formation of inflammasomes and pyroptosis 37 , or cell damage induced by a cytolytic peptide toxin (Candidalysin ECE1 ) 38 . Our analysis of single cells revealed bimodal expression in genes involved in these processes, and time analysis suggests that an initial shift in expression of filamentation and cell-wall remodeling programs in phagocytosed C. albicans rapidly result in down-regulation of the pro-inflammatory state of the host cells.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of the ECE1 locus or the region specifically encoding for candidalysin results in severe attenuation of pathogenicity in multiple infection models, including murine invasive and oral candidiasis, zebrafish swim bladder infection, and a variety of cell culture systems [77,[80][81][82][83]. Similarly, deletion of ECE1 or candidalysin significantly reduces immunopathologic markers of infection (neutrophils, pro-inflammatory cytokines, alarmins) and tissue damage during experimental VVC (Figure 1) [81].…”
Section: An Indispensable Role For Candidalysinmentioning
confidence: 99%
“…However, in the absence of hyphae formation, candidalysin did not induce phagosomal membrane rupture. Moreover, candidalysin is both a trigger for both NLRP3 inflammasome activation and a driver for inflammasome‐independent cytolysis of macrophages and dendritic cells (Kasper et al, ). Deciphering the biology associated with candidalysin will require further studies and will significantly enhance our collective understanding of C. albicans pathogenic potential.…”
Section: Candidalysin the First Pore‐forming Toxin Identified In Thementioning
confidence: 99%
“…Moreover, candidalysin is both a trigger for both NLRP3 inflammasome activation and a driver for inflammasome-independent cytolysis of macrophages and dendritic cells (Kasper et al, 2018).…”
Section: Candidalysin the First Pore-forming Toxin Identified In Tmentioning
confidence: 99%